Development and Application of the Anti-High-Temperature Delayed Crosslinking Polymer as a Gel Plugging Additive for Drilling Fluid - Quanyang Wang; Jing Cai; Jiannan Wang; Chenghua Zhou; Xinxin Wen; Jiang Zhang; Hui Mao (Gels, 2024)
With the gradual deepening of the exploration and development of deep and ultra-deep oil and gas resources, the problem of lost circulation in drilling operations is becoming more and more complex. From field experience, conventional plugging materials cannot fully meet the technical requirements of plugging operations in drilling engineering. In this study, a high-temperature- and salt-resistant polymer HDZ−A was synthesized. A high-temperature and delayed crosslinking polymer gel plugging agent can be prepared by adding a certain concentration of a crosslinking agent and a retarder. In this paper, the optimum synthesis conditions of the HDZ−A were determined with orthogonal experiments using viscoelasticity and viscosity as evaluation criteria for newly developed polymers. The molecular structure, temperature resistance, and relative molecular mass of HDZ−A were determined using infrared spectroscopy, nuclear magnetic resonance spectroscopy, and gel permeation chromatography. In addition, the optimal formula of the gel plugging agent was determined using gel strength as the evaluation standard. The results show that the newly developed gel plugging agent has stable performance after high-temperature crosslinking, and can resist high temperatures of 160 °C during formation. Under conditions of 160 °C, the gelation time can reach 4.5 h, and the plugging efficiency can reach more than 97%. Finally, the field test of the newly developed high-temperature-resistant delayed crosslinking polymer gel plugging agent was carried out in the direct exploration well KT-14X in the Ordos Basin. The field test showed that the plugging effect of the HDZ−A gel plugging agent was remarkable.